ANALISIS TANGGUNG JAWAB BANK TERHADAP NASABAH PADA PRODUK INVESTASI REKSADANA - Herman, Emillia; Lesatari, Rika; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Besides banks as intermediaries in capital markets, is used as a place to deposit funds of its customers, the storage function is referred to as the custodian bank. In fact some of the Bank transferred all responsibility to the customer. Based on this, the authors are interested in doing legal research shaped thesis with the title "Analysis of the Responsibilities Bank to the Customer on Mutual Mund Investment Products". The purpose of this research to determine the responsibility of the Bank and determine legal consequences for the Bank which transferred all of the responsibility to the Customer. This study use normative research method that emphasizes the principle of legal equality. Bank responsibilities arise if there are errors or omissions bank in maintaining and taking care of customer funds, as defined in rule legislation in the field of mutual funds. Legal consequences for banks which transferred the entire responsibility to the customer is null and void and the bank should be responsible to restore the Customer to same situation with there never was an agreement. Banks that are still expected to perform the entire transfer of responsibility to the customer can improve its internal regulations to make it same with mutual fund’s law in Indonesian. It is hoped that a more litigious Customer, so they can choose a bank that does not include a clause on transfer of all responsibility to the Customer, it is certainly also can encourage banks not to transfer the entire responsibility of the customer.Keywords: Responsibility Bank - Investment Products - Mutual Funds.